2023
DOI: 10.1037/npe0000173
|View full text |Cite
|
Sign up to set email alerts
|

Provincial marketization and individual financial literacy in China.

Abstract: In the past decades, China has experienced a process of marketization, but the levels of marketization in each province are imbalanced. The present research examines how provincial-level marketization predicts individual-level financial literacy in China by investigating a nationally representative sample with a set of standardized financial literacy tests. The results showed a positive association with a diminishing return between marketization and the Homo economicus index of financial literacy, including fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Extensive research has established that priming individuals to contemplate money or engaging in market activities leads to more unethical and individualistic behaviours and less prosocial behaviours (Falk & Szech, 2013;Vohs et al, 2006;Zhang & Xin, 2019). By considering evidence of the two conflicting views, we have found that there is more evidence suggesting the negative effects of the market mindset (Xin et al, 2022;Xin & Yang, 2023). Also, the majority of studies demonstrating the positive role of the market mindset in prosocial behaviour are predominantly correlational rather than causal in nature, thereby prohibiting the elimination of the influence of other variables (Xin, 2019).…”
Section: R E G U L a R A R T I C L Ementioning
confidence: 79%
“…Extensive research has established that priming individuals to contemplate money or engaging in market activities leads to more unethical and individualistic behaviours and less prosocial behaviours (Falk & Szech, 2013;Vohs et al, 2006;Zhang & Xin, 2019). By considering evidence of the two conflicting views, we have found that there is more evidence suggesting the negative effects of the market mindset (Xin et al, 2022;Xin & Yang, 2023). Also, the majority of studies demonstrating the positive role of the market mindset in prosocial behaviour are predominantly correlational rather than causal in nature, thereby prohibiting the elimination of the influence of other variables (Xin, 2019).…”
Section: R E G U L a R A R T I C L Ementioning
confidence: 79%